The Relationship Between Knowledge and Attitude with Personal Hygiene Behavior During Menstruation - Safitri, Anisa; Muslim, burhan; Alkafi (CV. CENDIKIA JENIUS INDONESIA, 2025)
Personal hygiene behavior during menstruation is an effort to maintain the cleanliness and health of the female reproductive organs during menstruation. Based on the reproductive health survey of Indonesian adolescents, nationally adolescents behave properly hygiene by 21.6%, while the behavior of adolescent girls in maintaining menstrual hygiene is still poor, which is 69.3%. The purpose of the study was to determine the relationship between the level of knowledge and attitude and personal hygiene behavior during menstruation in adolescent girls at SMP Negeri 25 Padang in 2025.This study is a quantitative research with a cross sectional design. The population in the study is all grade VIII students at SMP Negeri 25 Padang. A sample of 58 respondents was used as a proportional random sampling method. This research was conducted in March – August. Data collection was carried out on May 26 – May 28, 2025. Data were collected using questionnaires, then analyzed using univariate and bivariate analysis with chi-square tests.The results showed that 46.6% of students had poor personal hygiene behavior, as many as 46.6% of students had low knowledge, and 44.8% had negative attitudes. Based on statistical tests, it was found that there was a significant relationship between knowledge (p = 0.0001) and attitude (p = 0.0001) and personal hygiene behavior during menstruation. It was concluded that the knowledge and attitude of female students had a relationship with personal hygiene behavior during menstruation.